2021
DOI: 10.3390/socsci10070268
|View full text |Cite
|
Sign up to set email alerts
|

The Participation of Children and Adolescents in the Protection System: The Case of the Spanish Legislation

Abstract: Children’s right to participation is enshrined in the Convention on the Rights of the Child (CRC), specifically in Article 12; however, the participation of children in the protection system continues to be a challenge. There is a need for a paradigm shift, in which children and adolescents (CA) are considered as active subjects of rights in all areas of their lives, and that means allowing them to participate in decisions that concern them. The study analysed 20 Spanish laws, both national and autonomous, tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 32 publications
0
8
0
2
Order By: Relevance
“…Youth and foster care policies and services are exclusively carried out by each region, and each region has a public department that is responsible for issuing protection orders for children at‐risk (Kosher et al, 2018). National Law 26/2015 regulates each region's child protection policies, aiming at ensuring an adequate legal framework for protection that is consistent with the international treaties ratified by the signatory countries, in particular the UNCRC (Massons‐Ribas et al, 2021). This law prioritises: (1) stable over temporary placements, (2) foster over residential care and (3) placements agreed to by parents and services over enforced placements.…”
Section: Child Welfare In Spainmentioning
confidence: 99%
“…Youth and foster care policies and services are exclusively carried out by each region, and each region has a public department that is responsible for issuing protection orders for children at‐risk (Kosher et al, 2018). National Law 26/2015 regulates each region's child protection policies, aiming at ensuring an adequate legal framework for protection that is consistent with the international treaties ratified by the signatory countries, in particular the UNCRC (Massons‐Ribas et al, 2021). This law prioritises: (1) stable over temporary placements, (2) foster over residential care and (3) placements agreed to by parents and services over enforced placements.…”
Section: Child Welfare In Spainmentioning
confidence: 99%
“…Thus, it is observed that, unlike what happens in the case of CA (Massons‐Ribas et al (2021)), the details of work with the family do not have a general legal framework that imposes, or even contemplates, their participation. In addition, not only in decision‐making but also much less in its construction process and subsequent impact.…”
Section: Resultsmentioning
confidence: 98%
“…The type of foster care in extended families predominates, with 12 115 cases compared with 6777 in another family (Ministerio de Derechos Sociales y Agenda 2030, 2020). This predominance of foster care in extended families can be justified, along with the absence of foster families, because it strongly extols family ties (Massons-Ribas et al, 2021).…”
Section: Legislation As a Framework For Family Participation In The C...mentioning
confidence: 99%
See 1 more Smart Citation
“…Although the different regulations implemented by all autonomous communities are consistent with the CRC, in the excercise of their powers, autonomous communities have developed autonomous legislation to protect and promote the rights of minors that significantly vary from one autonomous community to another, in relation to the process of detecting risk situations, declaring abandonment, determining and implementing protection measures, and processing protection cases. As pointed out by some recent studies, this lack of harmonisation among the autonomous communities legislative frameworks generates important difficulties for professionals when implementing protection measures (for more details see Massons-Ribas et al 2021).…”
Section: The Legal Status Of Unaccompanied Minors In Spainmentioning
confidence: 99%